Investigation of deleterious effects of nsSNPs in the POT1 gene: a structural genomics‐based approach to understand the mechanism of cancer development. Issue 6 (16th December 2018) - Amir, Mohd.; Kumar, Vijay; Mohammad, Taj; Dohare, Ravins; Hussain, Afzal; Rehman, Md. Tabish; Alam, Perwez; Alajmi, Mohamed F.; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz
Abstract: Protection of telomere 1 (POT1) is one of the key components of shelterin complex, implicated in maintaining the telomere homeostasis, and thus stability of the eukaryotic genome. A large number of non‐synonymous single nucleotide polymorphisms (nsSNPs) in the POT1 gene have been reported to cause varieties of human diseases, including cancer. In recent years, a number of mutations in POT1 has been markedly increased, and interpreting the effect of these large numbers of mutations to understand the mechanism of associated diseases seems impossible using experimental approaches. Herein, we employ varieties of computational methods such as PROVEAN, PolyPhen‐2, SIFT, PoPMuSiC, SDM2, STRUM, and MAESTRO to identify the effects of 387 nsSNPs on the structure and function of POT1 protein. We have identified about 183 nsSNPs as deleterious and termed them as "high‐confidence nsSNPs." Distribution of these high‐confidence nsSNPs demonstrates that the mutation in oligonucleotide binding domain 1 is highly deleterious (one in every three nsSNPs), and high‐confidence nsSNPs show a strong correlation with residue conservation. The structure analysis provides a detailed insights into the structural changes occurred in consequence of conserved mutations which lead to the cancer progression. This study, for the first time, offers a newer prospective on the role of POT1 mutations on the structure, function, and their relation to associated diseases. Abstract : We have identified about 183 non‐synonymous single nucleotide polymorphisms (nsSNPs) as deleterious and termed as "high‐confidence nsSNPs." Distribution of these high‐confidence nsSNPs demonstrates that mutation in oligonucleotide binding domain 1 is highly deleterious (one in every three nsSNPs) and also show a strong correlation with residue conservation.